2011
DOI: 10.1111/j.1600-0889.2011.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new particle and secondary aerosol formation during summertime in Beijing, China

Abstract: A B S T R A C T Size-resolved aerosol number and mass concentrations and the mixing ratios of O 3 and various trace gases were continuously measured at an urban station before and during the Beijing Olympic and Paralympic Games (5 June to 22 September, 2008). 23 new particle formation (NPF) events were identified; these usually were associated with changes in wind direction and/or rising concentrations of gas-phase precursors or after precipitation events. Most of the NPF events started in the morning and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 60 publications
3
26
0
Order By: Relevance
“…8). The particle GR varied from 1.4 to 7.5 nm h −1 at 260 m and from 1.5 to 6.1 nm h −1 at ground level, which generally falls within the range that was reported previously in various environments, e.g., Beijing (Wu et al, 2007;Zhang et al, 2011), Shangdianzi , Egbert (Pierce et al, 2014), Marseille (Kulmala et al, 2005), and New Delhi (Sarangi et al, 2015). Particle growth rates strongly depend on temperature and the availability of condensable vapors.…”
Section: Chemistry Of Particle Growthmentioning
confidence: 58%
See 1 more Smart Citation
“…8). The particle GR varied from 1.4 to 7.5 nm h −1 at 260 m and from 1.5 to 6.1 nm h −1 at ground level, which generally falls within the range that was reported previously in various environments, e.g., Beijing (Wu et al, 2007;Zhang et al, 2011), Shangdianzi , Egbert (Pierce et al, 2014), Marseille (Kulmala et al, 2005), and New Delhi (Sarangi et al, 2015). Particle growth rates strongly depend on temperature and the availability of condensable vapors.…”
Section: Chemistry Of Particle Growthmentioning
confidence: 58%
“…Yue et al (2009) also found a clear shift of maximum diameter from 60 nm on clean days to 80 nm during polluted days. Most previous studies focused on new particle formation and growth events (NPEs) (Wehner et al, 2004;Wu et al, 2011;Gao et al, 2012;Zhang et al, 2011). While new particle formation (NPF) events are mostly observed under conditions with low relative humidity and clean air masses (Wu et al, 2007;Wehner et al, 2004), particle growth events are strongly associated with high relative humidity (Gao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the behavior of CN and CCN over East Asia and its outflow region, including spatial and temporal variations of CN and CCN concentrations, NPF frequency, and the contributions of primary and secondary particles, is of great importance. Various measurements related to NPF have been carried out previously in East Asia and over the western Pacific, for example, surface measurements in China [ Wehner et al ., ; Wu et al ., ; Liu et al ., ; Yue et al ., , , ; Wiedensohler et al ., ; Gong et al ., ; Shen et al ., ; Zhang et al ., ] and Korea [ Lee et al ., ; Song et al ., ; Yum et al ., ; Kim et al ., ] and aircraft measurements during the TRACE‐P and ACE‐Asia campaigns [ Weber et al ., ; McNaughton et al ., ; Buzorius et al ., ]. Few three‐dimensional modeling studies, however, have focused on NPF and its impact on CN and CCN concentrations in East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, many projects have had a rather campaign character, presenting only a few weeks of observations. The published studies have concentrated on the Beijing area (e.g., Yue et al, 2011;Gao et al, 2012;Zhang et al, 2011), Pearl River Delta, including Hong Kong (e.g., Liu et al, 2008;Gong et al, 2010;Yao et al, 2010), and urban areas in general (e.g., Gao et al, 2007Gao et al, , 2011Xu et al, 2011), but with few data on background sites (e.g., Guo et al, 2012). For example, the Yangtze River Delta (YRD) -a hotspot of human activity with its cumulative population of about 100 million people, the largest conglomerate of adjacent megacities in the world, and one of the motors of Chinese industrial development and -has seen only little research activity in terms of aerosols and their formation in the atmosphere (e.g., Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%